2016
DOI: 10.3171/2016.6.jns16537
|View full text |Cite|
|
Sign up to set email alerts
|

A prospective randomized trial of the optimal dose of mannitol for intraoperative brain relaxation in patients undergoing craniotomy for supratentorial brain tumor resection

Abstract: OBJECTIVE Mannitol is used intraoperatively to induce brain relaxation in patients undergoing supratentorial brain tumor resection. The authors sought to determine the dose of mannitol that provides adequate brain relaxation with the fewest adverse effects. METHODS A total of 124 patients were randomized to receive mannitol at 0.25 g/kg (Group A), 0.5 g/kg (Group B), 1.0 g/kg (Group C), and 1.5 g/kg (Group D). The degree of brain relaxation was classified according to a 4-point scale (1, bulging; 2, firm; 3, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 16 publications
0
14
2
1
Order By: Relevance
“…22,38 In contrast to our study, people receiving MAN during intracranial tumor resection show prolonged increases in serum potassium concentrations up to 180 minutes postinfusion. However, the administered MAN doses were higher at 1.5 g/kg IV, 38 In the HTS group, plasma ionized calcium concentration did not differ significantly from baseline at any sampling time point, but decreased below RI after HTS administration. In the MAN group, plasma ionized calcium concentration decreased significantly but transiently by T 5 and then increased to concentrations higher than baseline, but this difference was not significant.…”
Section: Plasma Electrolyte Concentrationscontrasting
confidence: 95%
See 1 more Smart Citation
“…22,38 In contrast to our study, people receiving MAN during intracranial tumor resection show prolonged increases in serum potassium concentrations up to 180 minutes postinfusion. However, the administered MAN doses were higher at 1.5 g/kg IV, 38 In the HTS group, plasma ionized calcium concentration did not differ significantly from baseline at any sampling time point, but decreased below RI after HTS administration. In the MAN group, plasma ionized calcium concentration decreased significantly but transiently by T 5 and then increased to concentrations higher than baseline, but this difference was not significant.…”
Section: Plasma Electrolyte Concentrationscontrasting
confidence: 95%
“…20,22,38 The most commonly cited mechanism for hyperkalemia development is cellular dehydration leading to increased intracellular potassium concentrations with a subsequent increase in passive potassium outflow from the intracellular space down its concentration gradient, and it is likely that it was also the primary mechanism at play in the dogs in our study. 22,38 In contrast to our study, people receiving MAN during intracranial tumor resection show prolonged increases in serum potassium concentrations up to 180 minutes postinfusion. However, the administered MAN doses were higher at 1.5 g/kg IV, 38 In the HTS group, plasma ionized calcium concentration did not differ significantly from baseline at any sampling time point, but decreased below RI after HTS administration.…”
Section: Plasma Electrolyte Concentrationsmentioning
confidence: 92%
“…The incidence of satisfactory brain relaxation (≥3 points) was significantly higher with dosages of 1.0 and 1.5 g/kg than with 0.25 g/kg, but this was not the case with a dosage of 0.5 g/kg. The proportions of satisfactory brain relaxation were 32.3% and 51.6% in the groups receiving 0.25 and 0.5 g/kg of 20% mannitol, respectively [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the principal mechanisms of action of mannitol is the promotion of a reduction in the volume of cerebral cells by creating an osmotic gradient between the interstitial and intravascular compartments [ 13 ]. Research in animals has shown a significant increase in ICP and cortical water content after a reduction in osmolality of 13 mOsm/kg [ 19 ], and it has also been suggested that a significant correlation exists between BRS and serum osmolality after mannitol administration (correlation coefficient: 1.43) [ 18 ]. Thus, the lack of a difference in BRS in our study may be explained by the absence of a significant difference in osmolality between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic BBBD has shown enhanceddelivery of therapeutic agents in other clinical trials 115–117,125,126 . Yet, challenges remain with this method that this is an invasive procedure requiring a multidisciplinary team to perform a complex technique and potential adverse effects can occur as seen in clinical studies are seizures, pulmonary edema, and renal failure 119,126–133 …”
Section: Strategies To Enhance Drug Penetrationmentioning
confidence: 99%